2006
DOI: 10.1186/1471-227x-6-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Ottawa Ankle Rules in Iran: A prospective survey

Abstract: BackgroundAcute ankle injuries are one of the most common reasons for presenting to emergency departments, but only a small percentage of patients – approximately 15% – have clinically significant fractures. However, these patients are almost always referred for radiography. The Ottawa Ankle Rules (OARs) have been designed to reduce the number of unnecessary radiographs ordered for these patients. The objective of this study was to validate the OARs in the Iranian population.MethodsThis prospective survey was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 25 publications
(19 reference statements)
1
28
0
Order By: Relevance
“…Thirty-four studies (in 33 articles) reported the accuracy of the Ankle Rules,7 19 22 24–27 29 32 35–37 39 44 46 48 49 53 56 60 62 65 67–69 74–77 79 80 82 84 15 studies (in 14 articles) reported the accuracy of the Midfoot Rules7 19 22 25 44 48 53 60 67–69 76 77 84 and for 31 studies it was not possible to distinguish between the ankle and midfoot, so a general Ankle/Midfoot Rules accuracy is provided20 21 23 28 30 31 33 38 40–43 45 47 50–52 54 55 57–59 61 63 66 70 71 73 78 83 85 (table 1 and figures 2 and 3). Pooled estimates of negative likelihood ratios and sensitivity were good, while positive likelihood ratios and specificity were poor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-four studies (in 33 articles) reported the accuracy of the Ankle Rules,7 19 22 24–27 29 32 35–37 39 44 46 48 49 53 56 60 62 65 67–69 74–77 79 80 82 84 15 studies (in 14 articles) reported the accuracy of the Midfoot Rules7 19 22 25 44 48 53 60 67–69 76 77 84 and for 31 studies it was not possible to distinguish between the ankle and midfoot, so a general Ankle/Midfoot Rules accuracy is provided20 21 23 28 30 31 33 38 40–43 45 47 50–52 54 55 57–59 61 63 66 70 71 73 78 83 85 (table 1 and figures 2 and 3). Pooled estimates of negative likelihood ratios and sensitivity were good, while positive likelihood ratios and specificity were poor.…”
Section: Resultsmentioning
confidence: 99%
“…The second sensitivity analysis looked at studies in which the entire sample was assessed using medical imaging as the reference standard, and included 25 studies (in 24 articles) for the Ankle,7 19 22 24–27 29 36 37 39 48 53 56 62 65 67 68 74 76 77 79 82 84 12 studies (in 11 articles) for the Midfoot7 19 22 25 48 53 67 68 76 77 84 and 22 studies for the Ankle/Midfoot Rules 20 28 31 33 40 41 45 50–52 54 55 57–59 61 66 70 71 78 83 85. Accuracy estimates were decreased in both sensitivity analyses when compared with the overall accuracies based on all studies (table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No studies were found that questioned the generalisablity of the OKR. However, clinical prediction rules may not perform as well when tested in a population other than that in which they were derived 1 12. Therefore, even well-defined decision-making rules are not suitable for application in all clinical settings without validation studies.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] As a result, the OAR have gained widespread acceptance throughout the world. [6][7][8][9][10] Numerous studies have examined nurses' interpretation and application of the OAR. [11][12][13][14] It is clear that the use of the OAR by nurses results in similar diagnostic performance for fracture detection as when the rules are applied by physicians, 15,16 and thus it is believed that emergency nurses can accurately determine which patients require radiographs in the setting of isolated blunt ankle injury.…”
Section: Introductionmentioning
confidence: 99%